Pengaruh Work-Life Balance dan Work Engagement terhadap Kepuasan Kerja dengan Fleksibilitas Kerja sebagai Variabel Moderasi pada Karyawan Generasi Z di Bandar Lampung - Rian Budi Utomo; Saputra, Febrian Eko (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the effect of Work-Life Balance and Work Engagement on Job Satisfaction, with Work Flexibility as a moderating variable among Generation Z employees in Bandar Lampung. Using a quantitative explanatory approach, data were collected from 190 respondents through purposive sampling and analyzed using multiple linear regression and Moderated Regression Analysis (MRA) with IBM SPSS. The results show that Work-Life Balance and Work Engagement have positive and significant effects on Job Satisfaction, while Work Flexibility does not significantly moderate these relationships. The model explains 69.8% of Job Satisfaction variance. Keywords: Work-Life Balance; Work Engagement;  Job Satisfaction; Work Flexibility; Generation Z